RETRACTED: Paris saponin VII enhanced the sensitivity of HepG2/ADR cells to ADR via modulation of PI3K/AKT/MAPK signaling pathway - Gong‐En Tang; Yue‐Xiang Niu; Yun Li; Chao‐Yu Wu; Xiao‐Ying Wang; Jian Zhang (Kaohsiung Journal of Medical Sciences)
Abstract To find the effect of Paris saponin VII (PS VII)‐mediated PI3K/AKT/MAPK signaling pathway on the sensitivity of ADR‐resistant HepG2 cell (HepG2/ADR) cells to ADR. The proliferation inhibitory rates were detected by using MTT assay. Flow cytometry was employed to examine the intracellular accumulation of ADR. The expressions of drug‐resistant genes (P‐gp, MRP and BCRP) were detected by qRT‐PCR, cell apoptosis by Annexin‐V‐FITC/PI staining, and the expressions of drug‐resistance‐related proteins, apoptosis‐related proteins, and PI3K/AKT/MAPK pathway‐related proteins were determined by Western blotting. HepG2/ADR and HepG2 cells treated with PS VII (0.88, 1.32, 1.98, and 2.97 μM) for 48 hours showed increased proliferation inhibitory rate in a dose‐dependent manner. HepG2/ADR cells treated PS VII (0.88, 1.32, 1.98 μM) for 48 hours showed decreased IC50 of ADR. Compared with HepG2/ADR cells treated with ADR (5 nM), those treated with PS VII (≤1.98 μM) and ADR (5 nM) showed enhanced ADR accumulation, decreased drug‐resistant gene expressions, increased cell apoptosis with unregulated Bax and cleaved caspase‐3 and downregulated Bcl‐2, as well as the inhibition of PI3K/AKT/MAPK pathway. Moreover, the combination of ADR (5 nM), PS VII (1.98 μM), and LY294002 (PI3K/AKT inhibitor, 20 μM)/SB203580 (P38 inhibitor, 20 μM) for 48 hours could further decreased the HepG2/ADR cell viability, but induced cell apoptosis, accompanying with the decreased expressions of drug‐resistant genes. PS VII could downregulate the expressions of drug‐resistance genes, increase intracellular accumulation of ADR, promote cell apoptosis, and enhance the sensitivity of HepG2/ADR cells to ADR via PI3K/AKT/MAPK.